1951
DOI: 10.1017/s0007485300027802
|View full text |Cite
|
Sign up to set email alerts
|

A Life-history Study of the Brown House Moth,Hofmannophila pseudospretella(Staint.) (Lep., Oecophoridae)

Abstract: Hofmannophila pseudospretella is widely distributed in this country. It is a minor pest of stored foodstuffs, clothes and furnishings, and under certain conditions may give rise to a major infestation.The egg stage is characterised by a high sensitivity to temperature and almost complete indifference to humidity. The incubation period varied from 110 days at 10°C. (90 per cent. R.H.) to 8·5 days at 27°C. (90 per cent. R.H.) and from 9·8 days at 90 per cent. R.H. (25°C.). to 14·0 days at 8·5 per cent. R.H. (25°… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1956
1956
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…In the case of the Brown House Moth, Hofmannophila pseudospretella (Stnt. ), a significant correlation has been traced between length of life and the weight of the female at emergence (Woodroffe, 1951).…”
Section: Length Of Lifementioning
confidence: 99%
“…In the case of the Brown House Moth, Hofmannophila pseudospretella (Stnt. ), a significant correlation has been traced between length of life and the weight of the female at emergence (Woodroffe, 1951).…”
Section: Length Of Lifementioning
confidence: 99%
“…Hofmannophila pseudospretella (Stainton) (Lepidoptera: Oecophoridae) (brown house moth) larvae are keratinophagous (Woodroffe 1951). They have a similarly low redox potential in the midgut as T. bisselliella but the pH is less alkaline (Christeller 1996).…”
Section: Introductionmentioning
confidence: 99%
“…sarcitrella requires conditions of <20 D C or 80% relative humidity to complete its life cycle, although individual stages will survive much lower conditions (W oodroffe 19 51 b). It can complete several generations a year in New Zealand, unlike H. pseudospretella which is usually univoltine and which, in northern Europe, overwinters as a fully grown larva in diapause (Woodroffe 1951a). Casual observation of cultures kept at the Lincoln Plant Health Station has shown that H. pseudospretella larvae also enter diapause during the southern hemisphere winter.…”
Section: Discussionmentioning
confidence: 99%